EP.FRI.510 The Management of Hyperkalaemia in Acute General Surgical Inpatients. (28th October 2021) - Karadaghi, Rezhaw; Sagar, Joseph; Bullingham, Roberta; Mathur, Pawan
Abstract: Aims: Hyperkalaemia is very common in hospitalised patients especially in peri-operative settings. It is associated with increased length of stay, morbidity and mortality. Here we review the management of hyperkalaemia in emergency surgery inpatients compared to the recommended national guidelines. With the identification of any gaps, we will introduce a new protocol to standardize practice as the basis of our educational intervention. Methods: A retrospective observational study of adult surgical inpatients between July and December 2020. 20 patients with a K +  >5.5 during their inpatient stay were identified. Data on their clinical management was extracted from their electronic data record and handover database and analysed. Results: Of the 20 patients identified, 13 had mild (5.5-6), 3 moderate (6-6.5) and 4 severe (>6.5) hyperkalaemia. Mortality was 0 and 100% of patients with K + ≥6.5 received timely emergency treatment in line with guidelines. However, there was a wide variation in the type of treatment given with 100% of cases not aligning with current guidelines. Additionally, in only 40% of cases was the hyperkalaemia documented and only 20% of patients received an ECG; a recommendation even in mild cases.  Conclusions: There is a need to standardise practice in the clinical management of hyperkalaemia and align with recent, validated guidance. A clear and easily accessible algorithm reinforced by an educational intervention to junior doctors may improve the management of high potassium in surgical inpatients and improve outcomes. Following this intervention, the standard will be re-audited.